Bureaucracies and networks organizational transformations in an Australian setting - Reyes, Vicente C. Jr. (2006)
The National Schools Network (NSN) is a national organizational innovation in Australia built around the professional community. NSN was created to significantly contribute to the creation of space for dialogue, collaboration and networking among members of the network. Among areas of improvements since its establishment are the creation of opportunities to experiment with innovative ideas, and provision of leading-edge resources and innovative education programs worldwide. NSN furthered teaching training and guaranteed professional development. Moreover, being hierarchical structures that characterized educational organizations due to collaboration and network practices. The impact of NSN, however, gave rise to new issues and challenges in education, particularly the flatenning of leadership which could rise to the end of bureaucracy in educational structure, and the policy influences of NSN in Australian education. In exploring these concerns, the theories of Weick (1976) and Cohen et al. (1983) underpin the argument.
Keywords: National School Network (Australia); Network governance